Knitting integral conformal all-textile strain sensor with commercial apparel characteristics for smart textiles. (June 2022) - Si, Shaobo; Sun, Chenchen; Qiu, Jing; Liu, Jing; Yang, Jin
Highlights: An ultra-stretchable, comfortable, and single-layer triboelectric all-yarn-based all-textile sensor (AATS) with an innovative alternating high elastic knitting structure was proposed. AATS not only exhibited excellent electrical performance but also performed the basic characteristics of commercial textiles. Combined with a mature seamless knitting technique, AATSs can be seamlessly integrated into a knitwear with promising aesthetics and comfort. A smart garment integrated with AATSs for unconstrained continuous breathing signal acquisition and sleeping position determination. Abstract: Combining traditional textile methods with electronic devices accelerates the development of wearable textiles in health and movement monitoring. Generally, using manufacturing methods of knitting yarns with heavy coatings or overlaying multi-layer fabrics rigidly do improve the performance of textile devices but trade off their characteristics of comfort and aesthetics, which hinders the practical and commercial promotion of wearable textiles. Using commercial knitting technology, we developed an all-yarn-based all-textile sensor (AATS) with good textile characteristics and electrical performance, which was presented in an innovative alternating high elastic structure for human health and motion monitoring. Taking full advantage of the knitted structure and special covered yarns, the AATS exhibited ultra-stretchability (up to 133%), wide working frequency bandwidth (0.5 Hz to 8 Hz), and high stability (over 10, 000 times), satisfying the need for sensitivity to capture the large range of deformation signals caused by human motion and respiration. It also fully meets the commercial apparel requirements of comfort, aesthetics and washability (50 cycles). Furthermore, AATSs can be seamlessly integrated into different parts of knitwear using mature seamless knitting technique. Such smart knitwear can accurately obtain and real-time monitor continuous human physiological activity signals and multi-dimensional sleeping status. This study investigated the potential of using commercial knitting technology to achieve smart textiles for comfort and personalization. Graphical abstract: Image, graphical abstract